2020
DOI: 10.18295/squmj.2020.20.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Deficiency in Diabetic Patients on Metformin Therapy: A cross-sectional study from Oman

Abstract: Objectives: This study aimed to determine the prevalence of vitamin B12 deficiency amongst diabetic patients on metformin therapy. Methods: This cross-sectional study was conducted at general clinics at the University Health Center and diabetes outpatient clinics at Sultan Qaboos University Hospital, Muscat, Oman, between January and December 2017. All Omani adults who were diagnosed with type 2 diabetes mellitus and took metformin were invited to participate in the study. The variables included in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
3
14
0
2
Order By: Relevance
“…[ 2 3 20 ] Metformin is perennially reported as a pharmacological cause of vitamin B12 deficiency. [ 4 5 6 7 8 9 10 21 ] The underlying mechanism is mostly controversial; proposed contributors have included competitive inhibition or inactivation of B12 absorption, alterations in intrinsic factor levels, gut bacterial flora, gastrointestinal motility, or ileal morphological structure, and interaction with the cubulin endocytic receptor. [ 21 22 ] Metformin is also shown to impair calcium-dependent membrane activity in the ileum, including uptake of the B12-intrinsic factor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 3 20 ] Metformin is perennially reported as a pharmacological cause of vitamin B12 deficiency. [ 4 5 6 7 8 9 10 21 ] The underlying mechanism is mostly controversial; proposed contributors have included competitive inhibition or inactivation of B12 absorption, alterations in intrinsic factor levels, gut bacterial flora, gastrointestinal motility, or ileal morphological structure, and interaction with the cubulin endocytic receptor. [ 21 22 ] Metformin is also shown to impair calcium-dependent membrane activity in the ileum, including uptake of the B12-intrinsic factor complex.…”
Section: Discussionmentioning
confidence: 99%
“…in 1969 and has been demonstrated by many researchers since then. [ 4 5 6 7 8 9 ] The reported prevalence of metformin-related vitamin B12 deficiency is widely variable (5--40%) in the available literature. [ 8 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…From the databases, I identified 7257 records; finally, 11 studies were included in this review [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Figure 1 shows the results of the screening and selection process.…”
Section: Resultsmentioning
confidence: 99%
“…The full results of the search are shown in Table 1 . Of the 11 scientific papers, 4 were conducted in the Kingdom of Saudi Arabia [ 16 , 18 , 19 , 21 ], 2 in Palestine [ 14 , 22 ], and 1 each in Libya [ 12 ], Lebanon [ 13 ], Qatar [ 15 ], Oman [ 20 ], and the United Arab Emirates (UAE) [ 17 ]. To the best of my knowledge, with this review, I am the first to explore the association between metformin use and vitamin B12 deficiency in individuals with T2DM in Arab countries.…”
Section: Resultsmentioning
confidence: 99%
“…14 Published literature and case reports have documented biochemical and clinical vitamin B12 deficiency to be highly prevalent among patients with type 1 and type 2 diabetes mellitus. [15][16][17] Metformin use has been unequivocally demonstrated as the prime factor associated with vitamin B12 deficiency among patients with T2DM. Cross sectional, retrospective, and longitudinal observational studies revealed evidence of vitamin B12 malabsorption in patients who had been treated with metformin for 3 months or in patients on longterm metformin therapy.…”
Section: Introductionmentioning
confidence: 99%